Thermal conductivity of spark plasma sintered SiC ceramics with Alumina and Yttria. Issue 6 (June 2021) - Chai, Zhenfei; Gao, Zhaohe; Liu, Han; Zhang, Xun; Glodan, Gyorgyi; Xiao, Ping
Abstract: In this study, dense SiC ceramics were fabricated at 1650−1750 °C for 10−60 min by spark plasma sintering (SPS) using 3−10 wt.% Al2 O3 -Y2 O3 as sintering additives. Effects of sintering temperature, sintering additive content and holding time on microstructure as well as correlations between microstructure and thermal conductivity were investigated. An increase in the sintering temperature promotes grain growth. Extending holding time has little influence on grain size but results in formation of continuous network of sintering additive, which increases interfacial thermal resistance and thus decreases thermal conductivity. For SiC ceramics composed of continuous SiC matrix and discrete secondary phase (yttrium aluminum garnet, YAG), an increase in the sintering additive content results in smaller grain size and lower thermal conductivity. The lower thermal conductivity of the SiC ceramic with higher sintering additive content is mainly due to the smaller grain size rather than the low intrinsic thermal conductivity of YAG.